Knowledge, Attitude and Practice of Elderly Outpatients with Type 2 Diabetes Mellitus in National Geriatric Hospital, Vietnam - Nguyen AT; Pham HQ; Nguyen TX; Nguyen TTH; Nguyen HTT; Nguyen TN; Dinh DTK; Phan HT; Nguyen SH; Tran BX; Latkin CA; Ho RCM; et al. (Diabetes, Metabolic Syndrome and Obesity, 2020)
Anh Trung Nguyen,1,2 Hai Quang Pham,3,4 Thanh Xuan Nguyen,1,2,5 Thu Thi Hoai Nguyen,1,2 Huong Thi Thu Nguyen,1,2 Tam Ngoc Nguyen,1,2 Dung Thi Kim Dinh,1 Hai Thanh Phan,3,4 Son Hoang Nguyen,6 Bach Xuan Tran,7,8 Carl A Latkin,8 Roger CM Ho,9,10 Cyrus SH Ho,9 Thang Pham,1,2 Huyen Thi Thanh Vu1,2 1Hanoi Medical University, Hanoi, Vietnam; 2National Geriatric Hospital, Hanoi, Vietnam; 3Institute for Global Health Innovations, Duy Tan University, Da Nang, Vietnam; 4Faculty of Medicine, Duy Tan University, Da Nang 550000, Vietnam; 5Dinh Tien Hoang Institute of Medicine, Hanoi, Vietnam; 6Center of Excellence in Health Services and System Research, Nguyen Tat Thanh University, Ho Chi Minh, Vietnam; 7Institute for Preventive Medicine and Public Health, Hanoi Medical University, Hanoi 100000, Vietnam; 8Bloomberg School of Public Health, Johns Hopkins University, Baltimore, MD, USA; 9Department of Psychological Medicine, Yong Loo Lin School of Medicine, National University of Singapore, Singapore, Singapore; 10Institute for Health Innovation and Technology (iHealthtech), National University of Singapore, Singapore, SingaporeCorrespondence: Huyen Thi Thanh VuDepartment of Geriatrics, Hanoi Medical University, 01 Ton That Tung, Hanoi, VietnamTel +84 913531579Email vuthanhhuyen11@hmu.edu.vnBackground: Diabetes-related complications have become increasingly prevalent and complicated to manage, especially among frail older adults with co-morbidities, poor physical function, and impaired cognition. Thus, knowledge, attitude, and practice (KAP) of elderly diabetic patients play an essential role in controlling the disease and its complications.Patients and Methods: A cross-sectional study was conducted on 176 diabetic patients at the outpatient clinics, National Geriatric Hospital, Hanoi, Vietnam from August to November 2015. Patients’ knowledge, attitude, and practice regarding diabetes mellitus were assessed using a structured questionnaire. Exploratory factor analysis and multivariate Tobit regression model were used to identify factors associated with knowledge, attitude, practice about diabetes mellitus.Results: Of 176 diabetic patients, patients’ knowledge was divided into two main groups: “Diabetes definition and management” (mean score = 57.7 ± 25.6) and “Targets for diabetic control” (mean score = 66.1 ± 30.4). Patients scored high points of attitudes toward diabetes severity and its complications (mean score = 95.8 ± 13.0); however, knowledge and practice scores were only moderate (mean score = 68.1 ± 16.8). There were only 8.5% of people having daily self-blood glucose monitoring. Advanced age, low educational level, rural area, and duration of diabetes less than 5 years were negative associated with knowledge, attitude, and practice regarding diabetes mellitus. This study also shows that frailty and co-morbidities/diabetic complications could impair patients’ knowledge.Conclusion: Older patients with diabetes had high levels of perceived severity attitudes on diabetes mellitus. However, the knowledge and practice levels were still inadequate. Pragmatic diabetic health literacy, counseling and education programs, as well as home-based treatments are viable options to improve health outcomes.Keywords: attitude, diabetes, elderly, knowledge, practice